A protocol for enumeration of aquatic viruses by epifluorescence microscopy using Anodisc™ 13 membranes - Budinoff, Charles R (BioMed Central, 2011)
BACKGROUND: Epifluorescence microscopy is a common method used to enumerate virus-like particles (VLP) from environmental samples and relies on the use of filter membranes with pore sizes < 0.02 μm; the most commonly used protocols employ 25 mm Anodisc™ membranes with a built-in support ring. Other filters with small pore sizes exist, including the 13 mm Anodisc™ membranes without a support ring. However, the use of these membranes for viral enumeration has not been previously reported. RESULTS: Here we describe a modified protocol for 13 mm Anodisc membranes that uses a custom filter holder that can be readily constructed in individual investigators' laboratories from commercially available Swinnex(® )filter holders. We compared VLP concentrations obtained from phage lysates and seawater samples using both Anodisc membranes, as well as Nuclepore™ small pore-size membranes (0.015 or 0.030 μm). The 13 mm Anodisc membranes gave comparable estimates of VLP abundance to those obtained with the 25 mm Anodisc membranes when similar staining methods were employed. Both Nuclepore membranes typically gave an order of magnitude lower VLP abundance values for environmental samples. CONCLUSIONS: The 13 mm Anodisc membranes are less costly and require smaller sample volumes than their 25 mm counterpart making them ideal for large-scale studies and sample replication. This method increases the options of reliable approaches available for quantifying VLP from environmental samples.